Effectiveness of pyramided genes in conferring resistance to anthracnose disease in common bean populations - Kiryowa, Moses J.; Nkalubo, Stanley T.; Mukankusi, Clare; Male, Allan; Tukamuhabwe, Phineas; Rubaihayo, P.; Gibson, Paul T. (Academic Journals, 2021)
Anthracnose disease (Colletotrichum lindemuthianum (Sacc. et. Magn) Lams. Scrib.) is one of the most devastating diseases that constrain common bean production in Uganda. A cascading pedigree pyramiding scheme was used to develop common bean populations to evaluate the effectiveness of pyramided and single resistance genes (Co-42, Co-43, Co-5, and Co-9) on disease development. Detached leaf trifoliates of F4:6 genotypes were screened with four C. lindemuthianum races (352, 713,767 and 2047). Disease severity data were subjected to ANOVA. Races, genotypes and Race x Genotype interaction were significant. Genes Co-42 and Co-5 conferred resistance to the four races and the gene pyramids Co-42+Co-5+Co-9 and Co-42+Co-5 had the lowest severity scores. Gene Co-43 conferred resistance to race 352 and weak resistance to race 713; whereas gene Co-9 conferred resistance to race 352. Co-43+Co-9 gene pyramid showed resistance only to race 352. The Co-42 and Co-5 genes conferred resistance to all the four races 352, 713, 767 and 2047. The single gene Co-42 was not significantly different from the pyramids Co-42+Co-5+Co-9 and Co-42+Co-5 (P<0.01). Similarly, the Co-5gene was not significantly different from Co-42+Co-5, Co-42+Co-9 and Co-5+Co-9 pyramids. The Co-9gene showed antagonism in all pyramids. These results indicate that pyramiding of resistance genes would be effective for disease management in Uganda, but pyramids with Co-9 gene would be less effective.